Network analysis of depressive symptoms in Chinese outpatients with somatic symptom disorder - Li, Yihui; Fang, Junning; Zhong, Yunhui; Li, Yibo; Liao, Yuanping; Tang, Hong (Frontiers in Psychiatry, 2025)
BackgroundSomatic symptom disorder and depression in clinical practice are strongly correlated. In this study, network analysis was used to assess the depressive symptoms of patients with somatic symptom disorder to identify the most core and influential symptoms. The aim of this study was to provide new perspectives for the treatment and rehabilitation of patients with somatic symptom disorder.MethodsA total of 899 individuals were enrolled from Gannan Medical University’s First Affiliated Hospital, Ganzhou People’s Hospital, and Third People’s Hospital of Ganzhou. A version of the Patient Health Questionnaire-9 was administered to assess symptoms of depression. We described the network structure of depressive symptoms, utilizing indicators of “strength,” “betweenness,” and “closeness” to identify the key symptoms within the network. A bootstrap approach with case-dropping was used to test the network’s stability.ResultsConcentration (PHQ7), Motor (PHQ8), and Anhedonia (PHQ1) symptoms had the highest centrality values, the strength values are 1.67, 1.62, and 1.58 respectively. The edge connecting sad mood (PHQ2) and energy (PHQ4) were the most influential in the model, with an edge weight of 0.69, the highest among all edges.ConclusionsThis network analysis study identifies distinct depressive symptomatology within the Chinese SSD patient population. Core symptoms anhedonia, cognition, and motivation primarily drive depressive symptoms, underscoring the need for clinical focus on these manifestations to prevent exacerbation. Tailored interventions targeting these core symptoms, including the integration of pleasant experiences, dopamine-based medications, attention bias modification training, and behavioral activation therapy, should be considered in treatment strategies.